THE ETHNIC SYSTEM OF THE CHECHENS IN THE CONTEXT OF MODERN SYNERGETICS (Revista Inclusiones, 2020)
The problem statement is due to the fact that the study of the behavior and development of ethnic groups in extreme situations has a scientific and practical importance and is poorly known until the present. The article aims to analyze the formation, development and behavior of the ethnic system of Chechens from the point of view of synergetics. The main approaches to the study of this problem were the principles of the modern synergetic concept and theory of ethnogenesis of Ln. Gumilev, which revealed that the elasticity and stability of the ethnic system of the Chechens to external influences was based on the dispersion and youthful stage.